Cytotoxicity of fluorographene. Issue 129 (17th December 2015) - Teo, Wei Zhe; Sofer, Zdeněk; Šembera, Filip; Janoušek, Zbyněk; Pumera, Martin
Abstract : Fluorinated graphenes (F-G) might inevitably be released into the environment through disposal and wearing of future commercial products incorporated with F-G. Therefore, we determined their cytotoxicity in this study. Abstract : Fluorinated graphenes (F-G) are gaining popularity in recent years and should they be introduced commercially in the future, these nanomaterials will inevitably be released into the environment through disposal or wearing of the products. In view of this, we attempted to investigate the cytotoxicity of three F-G nanomaterials in this study, with the use of two well-established cell viability assays, to find out their impact on mammalian cells and how their physiochemical properties might affect the extent of their cytotoxicity. Cell viability measurements on A549 cells following 24 h exposure to the F-G revealed that F-G does impart dose-dependent toxicological effects on the cells, and the level of cytotoxicity induced by the nanomaterials differed vastly. It was suggested that the fluorine content, in particular the types of fluorine-containing groups present in the nanomaterial played significant roles in affecting its cytotoxicity. In addition, control experiments which were conducted for possible nanomaterial-induced artifacts on the cell viability assays showed that absorbance readouts from the cell viability assays are free from interference from the nanomaterials.